Digitalisation and the labour market: Worker-level evidence from Slovenia - Miho, Antonela (OECD Economics Department Working Papers, 2023)
This paper provides evidence on the effects of digitalisation on the labour market in Slovenia using a unique dataset of Slovenian workers and firms for the years 2016 to 2020. Results show that at the firm level, digitalisation - measured in terms of ICT investment, is associated with positive and statistically significant effects on employment. However, job growth is not evenly distributed: High-skilled workers and younger workers benefit the most from employment gains, whereas there is little to no employment increases for low- and medium-skilled workers and older workers aged 50 or more. Furthermore, employment effects from digitalisation are strongest for private manufacturing firms. In contrast, ICT investment by state-owned firms is not associated with employment gains